Mediterrani i apocalipsi en la literatura catalana de ciència-ficció. - MARTÍNEZ-GIL, VÍCTOR (Scripta)
The aim of this paper is to analyse the presence of Mediterraneanism, that is, a collective identification way of thinking, in Catalan science-fiction literature about the end of the world. The paper lays out the possible relationships between what causes the apocalypse (a destructive world war, an alien invasion, environment issues) and the different portraits of the Mediterranean as the sanctuary of classical and life values (literature after the Spanish Civil War and until the 70s), as the portrait of a lost society (literature of the Exile period and 70s eco-fiction), or as a menacing water body or a subject of new identity values in apocalyptic climate fiction and Anthropocene fiction. This paper can help understand the ideological changes that happened between the Cold War, Postmodernity, and the present time.